Kearifan ekologis dalam cerita rakyat tentang sumber air di Kabupaten Klaten - Ramadhani, Asri Kamila; Sumarwati, Sumarwati; Setiawan, Budhi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Folktales about water sources in Klaten have not been widely accessed, causing values related to environmental conservation and water sustainability to be insufficiently conveyed. The purpose of this research is to inquire into the ecological knowledge contained in Klaten folktales about water sources and how they might be used to teach Indonesian language skills to junior high school students. This study takes an ethnographic approach to its qualitative descriptive methodology. Water sources and associated folktales were the focus of the research in six subdistricts of Klaten. Using purposive and snowball sampling approaches, data was collected from a variety of sources, including village leaders, cultural figures, local citizens, and relevant authorities. Triangulation of methods and sources was used to verify the data collected from in-depth interviews. An interactive model was used for data analysis. A number of ecological wisdom principles, including cosmic solidarity, concern for nature, environmental preservation, justice, and moral integrity, are included in the folktales, according to the research. The dominant ecological wisdom value is the principle of living simply and in harmony with nature, as manifested in the story of Roro Amis, who sailed on a banana trunk, and Prince Sidotopo, who played the traditional game nglarak blarak.